Fenomena Baby Boom dan Dampaknya pada Populasi Jepang Masa Kini - Yessy Harun; Robihim Robihim; Uly Lulu Qur’ani (Universitas Al Azhar Indonesia, 2022)
The baby boom phenomenon is a condition of the Japanese population surge that occurred from 1947 to 1949. This was due to the decline in the Japanese population due to the bombing of the cities of Hiroshima and Nagasaki by the United States in 1945 which killed 90,000-146,000 people in Hiroshima and 39,000-80,000 people in Nagasaki. This condition resulted in all Japanese soldiers being withdrawn from the war and returning to civilian life. Life changes make residents focus on family matters, consequently causing a situation of explosive population increase of up to 5% every year. The purpose of this research is to reveal the baby boom phenomenon and its impact on 2018. Through the ethnographic method, the author examines the period of the baby boom generation, from the beginning of birth to the present. The research data were obtained from sources related to the early days of the baby boom generation to date. The results of this study, that the baby boom phenomenon, causes a very high level of competition from entering the preschool period to entering the world of work. As a result, this competition has an impact on maintaining life, thus ignoring marriage, which has an impact on the decline Japanese population in 2018.Keywords - Baby Boom Phenomenon, Impact, Japan's Population